Colour Doppler Ultrasonography as a Tool to Assess Luteal Function in Santa Ines Ewes - Figueira, L. M.; Fonseca, J. F.; Arashiro, E. K. N.; Souza-Fabjan, J. M. G.; Ribeiro, A. C. S.; Oba, E. [UNESP]; Viana, J. H. M.; Brandao, F. Z. (Wiley-Blackwell, 2015)
Contents The aim of this study was to evaluate luteal dynamics in the Santa Ines ewes using colour Doppler (CD) ultrasonography. Oestrus was synchronized in nulliparous females (n=18), and subsequently, they were only teased (n=6) or teased and mated (n=12). Blood samples were collected daily for plasma progesterone (P-4) concentrations. Ultrasonographic images of corpora lutea (CL) in CD mode were obtained for further analysis in its largest diameter. The CD mode allowed an early sequential monitoring of CL that was visualized by the first time 0.77 +/- 0.62days after ovulation, with luteal area 29.68 +/- 13.21mm(2). During the luteogenesis, a progressive increase was observed, followed by a plateau of luteal area, vascularization area and plasma concentrations of P-4 reaching maximum values in D11 (124.0 +/- 38.0mm(2), 52.78 +/- 24.08mm(2) and 11.23 +/- 4.89ng/ml, respectively). In the luteolysis, the plasma concentrations of P-4 decreased sharply, whereas luteal and vascularization area gradually. The vascularization area was positively correlated with plasma concentrations of P-4 during the luteogenesis (r=0.22) and luteolysis (r=0.48). The luteal dynamics of Santa Ines ewes showed patterns similar to those observed in other sheep breeds studied. The CD ultrasonography has the potential to be used as a tool to assess luteal function in sheep.